Interpolação de eventos de reflexão em traços sísmicos de dados pré-empilhamento usando aproximação de tempo de trânsito SRC-AF - FERNANDES, Alexandre Sodré (Universidade Federal do Pará, 2019)
The seismic method is a well known technique for revealing details of the geological subsurface structures because the seismic data are processed and produce seismic sections, which are images of subsurface structures. The quality of the recorded seismic data depends on factors such as the complexity of the subsurface, level of noise, surface topography of acquisition, heterogeneities in the mantle of weathering, among others. Irregular acquisition, short offsets, low coverage in common points in depth lead to a low quality imaging in subsurface and low resolution in seismic sections. In common reflection surface imaging, the hyperbolic approximation of traveltimes for paraxial rays in the vicinity of a central ray reflected with finite source-receiver offset, function of five kinematic attributes of the wave field, represent better the time field reflection compared to conventional methods. The Common Reflection Surface for Common Offset (CRS-CO) approaches reflection events within the vicinity of the trace with a fixed offset that we want to interpolate, adding correlated events, where the output is defined as the weighted average of the amplitudes along the traveltime approximation SRC-AF, assigning the result to its trace to all points of an common offset section. The specific objective of this work is to model the regularization of temporal sections filling areas lacking seismic data, increasing the signal to noise ratio by interpolation of reflection events in seismic traces based on the approximation of traveltime for Common Reflection Surface for Common Offset (CRS-CO). The algorithm was applied to the seismic acquisition settings Common Source, Common Offset and Common Mid Point for a set of 2D synthetic data, modeled by ray tracing.